LISTEN-READ-DISCUSS IN TEACHING AND LEARNING READING COMPREHENSION: A CASE STUDY OF PRIVATE SENIOR HIGH SCHOOL IN LAMPUNG - Rija Dwiono (Universitas Sebelas Maret, 2017)
Listen-Read-Discuss (L-R-D), a strategy which has been found to be a powerful means of improving reading comprehension by prominent experts. On the contrary, the students at Private Islamic Senior High School in Lampung who achieved scores above the minimum standard of competency was under half of total amount. This showed there was a contra-side between the theories and the implementation. A descriptive qualitative study was carried out by using case study investigating on L-R-D implementation. The data were obtained from observation, questionnaire and interview. The data which were analized qualitatively, inductively and interpretively, resulted in three emerging issues: the several weaknesses during the process of L-R-D implementation in reading comprehension class and the problems faced by the teacher and the students in teaching and learning reading comprehension by using L-R-D.